PENGARUH PERMAINAN JEMBATAN TAPANULI TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK ADHYAKSA XXVI PADANG - Nanda Sari Musril, Putri; Hazizah, Nur; Yulsyofriend; Pransiska, Rismareni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to ascertain how the Tapanuli bridge game affects the speaking skills of the students at Adhyaksa XXVI Kindergarten in Padang. This study employs a “nonequivalent control group design, a quasi-experimental method, and a quantitative methodology. Twenty-four youngsters were used as research subjects, and they were split into two groups: the experimental class and the control class”. While the control group received traditional instruction, the experimental group received treatment in the form of the Tapanuli bridge game. Speaking ability tests, structured observations, and documentation were used as data gathering methods. The SPSS version 26 software was used to “analyse the data using the t-test (independent sample t-test), homogeneity tests, and normality tests”. The findings indicated that there was a “significant difference between the children's speaking abilities in the experimental class and the control class, with a significance value (Sig. 2-tailed) of 0.000 <0.05. Therefore, it can be said that the Tapanuli bridge game significantly and favourably enhances children's speaking skills between the ages of five and six. The study's findings show that traditional games can be used as an alternative, effective learning activity to help children who are the study's target improve their speaking abilities. Additionally, this game is enjoyable and significant in helping young children develop their speaking abilities”.